2023
DOI: 10.1021/acs.molpharmaceut.3c00226
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Novel Coamorphous Salt Formulation of Telmisartan with Amlodipine to Enhance Permeability and Oral Absorption

Abstract: Coamorphous formulation is a useful approach for enhancing the solubility of poorly water-soluble drugs via intermolecular interactions. In this study, a hydrogen-bondingbased coamorphous system was developed to improve drug solubility, but it barely changed the apparent permeability (P app ) of the drug. This study aimed to design a novel coamorphous salt using ionic interactions to improve drug permeability and absorption. Telmisartan (TMS), with an acidic group, was used to form a coamorphous salt with basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Coamorphous systems are homogeneous single amorphous systems comprised by two or more low-molecular-weight molecules. , For pharmaceutical formulation development, coamorphous systems are remarkably interesting since they increase the solubility of the API without the stability problems associated with amorphous materials. , In this work, a new coamorphous of RIF with TRIS with a RIF–TRIS ratio of 2:1 (Figure ) was developed and characterized. RIF is a low-solubility API and therefore a suitable candidate for a solubility increase.…”
Section: Discussionmentioning
confidence: 99%
“…Coamorphous systems are homogeneous single amorphous systems comprised by two or more low-molecular-weight molecules. , For pharmaceutical formulation development, coamorphous systems are remarkably interesting since they increase the solubility of the API without the stability problems associated with amorphous materials. , In this work, a new coamorphous of RIF with TRIS with a RIF–TRIS ratio of 2:1 (Figure ) was developed and characterized. RIF is a low-solubility API and therefore a suitable candidate for a solubility increase.…”
Section: Discussionmentioning
confidence: 99%
“…WO/2007/147889 and US 6737432 described the preparation of telmisartan salt with sodium [16] and organic acids [17]. Recently, Hatanaka et al reported a co-amorphous drug-drug salt between telmisartan and amlodipine with an improved solubility and permeability for oral absorption [18]. Research has also been conducted to investigate the formation of telmisartan salt with the addition of hydrochloric acid (HCl), which shows an increase in solubility [19].…”
Section: Introductionmentioning
confidence: 99%
“…TEL (Figure ), characterized by high permeability and pH-dependent low aqueous solubility (0.09 μg/mL), belongs to the BCS class II drug category, with a dissolution rate-limited oral bioavailability of 40–58% . TEL is considered as a high glass forming molecule with a moderate glass stability and several strategies like use of polymers in conjunction with alkalizers, , antisolvent crystallization, development of cocrystals, and coamorphous systems have been investigated to inhibit recrystallization of amorphous TEL (AM-TEL) to maximize its solubility and dissolution profile. Most recently, Bennett et al and Sharma et al .…”
Section: Introductionmentioning
confidence: 99%